Resiliensi Individu Pada Film Sleep Call Karya Fajar Nugros - Ramadhan, Zhefind; Hariyati, Farida; Setiawati, Titin (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2024)
ABSTRACTThe movie Sleep Call tells the story of Dina (Laura Basuki) as the main character in the movie. Dina does not have someone who can be relied upon in dealing with her various problems. This study aims to describe the resilience of individuals contained in the movie Sleep Call. The type of research used is a descriptive qualitative approach with observation and documentation techniques. The data analysis technique uses the theory of resilience by Reivich Shatte which includes 5 aspects of resilience, namely; emotion regulation, impulse control, problem cause analysis, and self-efficacy. The results of this study found 10 scenes of resilience aspects, respectively 1 scene of emotion regulation aspects, 3 scenes of impulse control aspects, 2 scenes of problem cause analysis aspects, 2 scenes of empathy aspects, and 2 scenes of self-efficacy aspects.Keywords :  Individual Resilience, Sleep Call Movie, Content Analysis ABSTRAKFilm Sleep Call mengisahkan Dina (Laura Basuki) sebagai pemeran utama dalam film tersebut. Dina tidak memiliki seseorang yang dapat diandalkan dalam menghadapi berbagai permasalahannya. Penelitian ini bertujuan untuk mendeskripsikan resiliensi individu yang terdapat pada film Sleep Call. Jenis penelitian yang digunakan adalah pendekatan kualitatif deskriptif dengan teknik observasi dan dokumentasi. Teknik analisis data menggunakan teori resiliensi oleh Reivich Shatte yang mencakup 5 aspek resiliensi yaitu; regulasi emosi, pengendalian impuls analisis penyebab masalah, dan efikasi diri. Hasil pada penelitian ini menemukan 10 adegan aspek resiliensi, masing-masing 1 adegan aspek regulasi emosi, 3 adegan aspek pengendalian impuls, 2 adegan aspek analisis penyebab masalah, 2 adegan aspek empati, dan 2 adegan aspek efikasi diri.Kata kunci : Resiliensi Individu, Film Sleep Call, Analisis Isi